Analisis Semiotika Self-Love (Mencintai Diri Sendiri) dalam Video Klip “Jiwa yang Bersedih “ Ghea Indrawari - Herri Setiawan (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
The purpose of this study is to apply self-love to help maintain mental health and reduce the risk of disorders in one's psychological condition in Ghea Indrawati's "Sad Soul" video clip. This analysis focuses on how the depiction of self-love is contained in each scene, then continues on Charles Sanders Peirce's semiotic model (triangle meaning). This research is qualitative research and uses semiotic analysis owned by Charles Sanders Peirce. For Charles Sanders Peirce, the fundamental principle of the nature of signs is representative and interpretive nature. The music video of the song "Sad Soul" was chosen because the music video has many moral messages aimed at loving yourself, this concept encourages someone to be able to recognize and accept themselves then be able to treat themselves well and as they are. The results of this study have 3 aspects, namely self-love as soft love for oneself that focuses on planting, nurturing, and developing oneself. Self-love as a dynamic state of self-appreciation, which grows from actions that support physical, psychological, and spiritual growth. Self-love as a feeling of comfort and the ability to set aside time for self-care.